Computational modelling of cell migration in confined environments - Royo, Víctor; García Aznar, José Manuel; Gómez Benito, Mª José (Jornada de Jóvenes Investigadores del I3A, 2017)
Cell migration has gained attention over the last years due to its key role in different physiological and pathological process such as embryonic development and tumour growth [1]. Many researchers have developed studies about what stimulate the cells and the critical point in the cell mobility. In this work, we consider cell migration in microchannels, simulating the exact moment when the cell cross to the veins.